The violence of forgetting: trauma and transnationalism in Coetzee's Dusklands. Issue 3 (15th April 2016) - Ng, Lynda
Abstract : Throughout his career, J.M. Coetzee has sought to resist national confines, preferring instead to emphasise the transnational aspects of culture and history. This essay examines the interplay between nation, transnationalism and literature in Coetzee's novel Dusklands, and shows how a fully formed ethics of violence can already be seen on display in his fictional debut. Key themes that become important throughout Coetzee's oeuvre are developed here – in particular, the abhorrence of violence in any form and a suspicion of the de-humanising elements of nationalism. This essay reads the war photographs in 'The Vietnam Project' and their ability to induce a form of post-traumatic stress disorder in the narrator Eugene Dawn as a commentary on the problem of complicity in the act of witnessing violence. The uncompromising stance that Coetzee adopts against nationally sanctioned acts of forgetting becomes clear in the way his novel spares no one from the net of complicity, showing how it extends not only to mediated images of atrocity but also to those who would refuse to bear witness to violence. Finally, the essay proposes the 'transnational wound' as an effective metaphor for understanding the transnational and its embedded relationship within national frameworks.